Cross‐Talk‐Suppressing Electrolyte Additive Enabling High Voltage Performance of Ni‐Rich Layered Oxides in Li‐Ion Batteries. Issue 11 (7th May 2021) - Pham, Hieu Quang; Nguyen, Minh Tri; Tarik, Mohamed; El Kazzi, Mario; Trabesinger, Sigita
Abstract: Control of electrode‐electrolyte interfacial reactivity at high‐voltage is a key to successfully obtain high‐energy‐density lithium‐ion batteries. In this study, 2‐aminoethyldiphenyl borate (AEDB) is investigated as a multifunctional electrolyte additive in stabilizing surface and bulk of both Ni‐rich LiNi0.85 Co0.1 Mn0.05 O2 (NCM851005) and graphite electrodes in a cell operated with elevated upper cutoff voltage of 4.4 V vs. Li + /Li. The presence of AEDB in a full‐cell inhibits structural degradation of both cathode and anode materials, suppressing crack formation, and reduces metal dissolution at the cathode and metal deposition at the anode. As a consequence, the interfacial resistance is significantly reduced. Moreover, this is a case where "the whole is greater than the sum of the parts": the effect of AEDB in half‐cells is rather modest, whereas in full‐cells its addition results in tremendous performance improvement. The graphite‖NCM851005 full‐cell in the presence of AEDB has a capacity retention of 88 % after 100 cycles, even when the upper cutoff voltage is set to 4.35 V, corresponding to 4.4 V vs Li + /Li, whereas with standard electrolyte under the same conditions it is only 21 %. The study shows a simple and easy approach to using Ni‐rich cathodes in an extended voltage window and demonstrates the importance of full‐cell testing for electrolyte additive selection. Abstract : No more talk : Multifunctional electrolyte additive 2‐aminoethyldiphenyl borate (AEDB) significantly improves long‐term cycling of a graphite‖LiNi0.85 Co0.1 Mn0.05 O2 full‐cell under an upper cutoff voltage of 4.35 V. The excellent electrochemical performance is attributed to the participation of AEDB in forming a stable surface protective film at the cathode and a solid–electrolyte interphase at the anode.